The effect of training attributes and the moderating role of changed behaviour on employee performance: an examination in the context of Malaysian hotels / Fadzilah Mohd Shariff - Mohd Shariff, Fadzilah (Institute of Graduate Studies, UiTM, 2013)
Research indicates that more than 80% of the knowledge and skills gained in training programs is not applied in the workplace, but there is growing body of evidence that recognizes managerial involvement as a primary factor in improving training transfer. Individual characteristics and work environment variables have been emphasized by research as important in the transfer of training, but it is surprising that little research has addressed the issue of the employees’ own individual characteristics and work environment variables as being significant in their ability to transfer their knowledge and skills gained from training back to the job. The purpose of the study is to examine the relationship among selected trainee characteristics variables and work environment variables in the process of behavioural change and effect on employee performance in the Malaysian hospitality industry. The two influential factors that emerged from the various learning transfer models were individual characteristics (e.g., motivation) and work environment (e.g., supervisor support, co-worker support, and the opportunity-to-use the available resources). The hypotheses and supporting logic for linkages between the variables are drawn from several research foundation and theories. The proposed hypotheses were tested with data collected from frontline restaurant service employees working in four and five star rating hotels in Kelang Valley, Malaysia. Confirmatory factor analysis (CFA) was utilized to assess the measurement model, and path analysis with structural equation modelling (SEM) was employed to test the proposed hypotheses. The results of the study showed that the proposed individual characteristics and work environment variables have a significant effect on frontline employees’ performance. Employees’ motivation and employees’ performance received strong support in a significant relationship (β: 0.778, t: 4.510, p<0.001)…